Transcoccygeal neurolytic ganglion impar block for perineal pain: A case series - K B Nalini; Shivakumar Shivanna; M S Vishnu; C. V. R. Mohan (Journal of Anaesthesiology Clinical Pharmacology, 2018)
Background and Aims: Chronic perineal pain (CPP) is a poorly localized pain. Its etiology may be benign or malignant. The ganglion impar is a solitary retroperitoneal structure at sacrococcygeal junction. It provides the nociceptive and sympathetic supply to the perineal structures. CPP has been effectively managed by ganglion impar block. Here, we describe a case series of neurolytic ganglion impar block by transcoccygeal approach, analyzing its safety and efficacy. Material and Methods: In this study, five consecutive patients who were given ganglion impar block for CPP using a transcoccygeal approach were followed up for 2 months. The visual analog scale (VAS) score for pain at presentation, time required for the pain to reduce by 50% after the block, VAS during a 2-month follow-up, time required to perform the procedure, number of attempts, and any complications were noted. Results: All the five patients had an excellent pain relief. The mean duration for decrease in VAS by 50% was 14.8 ± 3.1 min. The mean duration to perform the procedure was 10.2 ± 1.5 min. There were no complications. All the patients had clinically significant pain relief with VAS score of 2 till 2-month follow-up. Conclusion: Transcoccygeal ganglion impar block may offer a safe and effective treatment option for CPP as compared to opioids. This approach for neurolysis of the ganglion impar may be recommended in view of the direct course, appreciable end point, and smaller volume of neurolytic requirement.